The discrete dipole approximation code DDscat.C++: features, limitations and plans - Choliy, V.Ya. (Advances in Astronomy and Space Physics, 2013)
We present a new freely available open-source C++ software for numerical solution of the electromagnetic waves absorption and scattering problems within the Discrete Dipole Approximation paradigm. The code is based upon the famous and free Fortan-90 code DDSCAT by B. Draine and P. Flatau. Started as a teaching project, the presented code DDscat.C++ differs from the parent code DDSCAT with a number of features, essential for C++ but quite seldom in Fortran. This article introduces the new code, explains its features, presents timing information and some plans for further development.